PREDICTION MODEL OF INUNDATION IN PUMPED-FIELD LOWLANDS AND SCENARIOS FOR IMPROVING ITS PERFOMANCE - N. Cao Don; H. Araki; H. Yamanishi; K. Koga (International Association of Lowland Technology, 2003)
During rainy season, frequent flooding by strom water is one of the most serious problems in lowland areas, causing heavy effect on transportation, agriculture, industry, and economic activities. As a result, the required drainage water levels in this area are generally lower than the water levels of boundary rivers. Under such circumstances, pumping system should be designed from a viewpoint of integrated control floods. The Nam Ha lowland, in Vietnam, bounded by four surrounding rivers, is selected as a case study. The operation scheme in this area is a key factor for drainage and flood protection. This developed mathematical model can be used as a tool to evaluate the present drainage system as well as flooding processes in the field as well as inundation areas and water levels along drainage channels. It is found that the proposed model can be applied to evaluate integrated flood control system for pumped-field lowland. Such an operating system provides an effective tool by means of which the drainage system can be operated appropriately taking into account of tidal effects, rainfall intensity, and reaching time of the rainwater.